2009
DOI: 10.19030/ajbe.v2i3.4048
|View full text |Cite
|
Sign up to set email alerts
|

Adding Value To The First-Year Experience: Embedding Self And Major Exploration In The College Of Business Curriculum

Abstract: <p>This paper details the First-Year Career Development Program (First-Year Program) a component of a comprehensive multi-year program designed to guide business students through self-assessment and the selection of an appropriate business major and ultimately to prepare them to secure professional career positions. The First-Year Program is designed to integrate student self-assessment and career and business major exploration into the First-Year Experience. A survey of students who participated in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 6 publications
1
6
0
1
Order By: Relevance
“…The results of this study suggest participation in a career intervention is a statistically significant predictor of a student graduating within 4 years, as suggested by the literature (Damminger, Potter, & Pritchard, 2009; Folsom et al, 2002; Reardon, Melvin, McClain, Peterson, & Bowman, 2015). One reason students do not graduate within 4 years is due to the lack of vocational identity clarity (Cuseo, 2005).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The results of this study suggest participation in a career intervention is a statistically significant predictor of a student graduating within 4 years, as suggested by the literature (Damminger, Potter, & Pritchard, 2009; Folsom et al, 2002; Reardon, Melvin, McClain, Peterson, & Bowman, 2015). One reason students do not graduate within 4 years is due to the lack of vocational identity clarity (Cuseo, 2005).…”
Section: Discussionsupporting
confidence: 78%
“…Beginning the intervention immediately when a matriculate enrolls in higher education was found to be effective. The results of this study and relevant research suggested it is beneficial to have students engage in developing their vocational identity during their first year of college (Damminger et al, 2009; Johnson et al, 2002). Likewise, following up with students after the career intervention is recommended to ensure the most positive response on increasing 1-year retention and 4-year graduation rates.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Many of the FYE courses described in the literature have attempted to address both frameworks (Damminger, Potter, & Pritchard, 2009). Courses often include discussions, reading assignments, and guest speakers which address both the strategies needed for academic success, and the needed information to socialize and integrate the new students into the university.…”
Section: Previous Researchmentioning
confidence: 99%